The Effect of Principal Leadership and Work Discipline on Teacher Performance at SMP Daruttaqwa Gresik - Rosmawati Rosmawati; Syafrida Hafni Sahir; Kersna Minan; Made Susilawati (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This article describes (1) the influence of a principal's leadership on teacher performance. (2) the effect of work discipline on teacher performance. (3) the simultaneous influence of the principal's leadership and work discipline on teachers' performance at SMP Daruttaqwa Gresik. The research method used is quantitative research. This study is a population study with 59 people—consisting of 1 principal, 12 teachers, 1 Administration (TU), and 46 students. The research instrument is a questionnaire. The results of this study are (1) there is an influence between the principal's leadership on teacher performance at SMP Daruttaqwa Gresik with t count 2,580 > t table 2.00 and has an effect of 10.5%. (2) there is an influence between work discipline on teacher performance at SMP Daruttaqwa Gresik with t count 7.924 > t table 2.00 and has an effect of 52.4%. (3) there is a simultaneous effect with F arithmetic 31.019 > F table 3.16. Simultaneously both of them also have an effect of 52.6% on teacher performance at SMP Daruttaqwa Gresik and have a correlation coefficient of 0.725, which is the quality of a strong relationship.